Web 2.0 as Syndication - Clarke,Roger (Universidad de Talca, 2008)
There is considerable excitement about the notion of ’Web 2.0’, particularly among Internet businesspeople. In contrast, there is an almost complete lack of formal literatura on the topic. It is important that movements with such energy and potential be subjected to critical attention, and that industry and social commentators have the opportunity to draw on the eCommerce research literatura in formulating their views. This paper assesses the available information about Web 2.0, with a view to stimulating further work that applies existing theories, proposes new ones, observes and measures phenomena, and tests the theories. The primary interpretation of the concept derives from marketers, but the complementary technical and communitarian perspectives are also considerad. A common theme derived from the analysis is that of ’syndication’ of content, advertising, storage, effort and identity.